The purity of vengeance [compact disc, unabridged] : a Department Q novel - Adler-Olsen, Jussi (Adler-Olsen, Jussi. Department Q novel., 2013)
Detective Carl Morck already has plenty on his mind when he is presented with the case of a brothel owner, and a woman named Rita, who went missing in the eighties. New evidence has emerged in the case that destroyed the lives of his two partners, the case that sent Carl to Department Q. But when Carl's assistants, Assad and Rose, learn that numerous other people disappeared around the same weekend as Rita, Carl takes notice.